Perbandingan Efektivitas Antibakteri Moringa oleifera dan Ziziphus mauritiana dengan Ekstrak Etanol 96% terhadap Escherichia Coli - Sania, Eli; Kurniawan, Sandy Vitria; Angelina, Yohanna (Sriwijaya Journal of Medicine, 2020)
Escherichia coli is a normal bacterium in the lower part of human digestion, but if the amount is above normal, E. coli will cause various diseases. Inappropriate use of antibiotics can cause resistance, so alternative treatments such as herbal medicines are needed. Herbal plants that have been explored as antibacterial compounds are Moringa oleifera leaves and Bidara leaves (Ziziphus mauritiana). This research was conducted to see the comparison of the antibacterial effectiveness of Moringa oleifera and Ziziphus mauritiana with 96% ethanol solvent against E.coli. The design of this study used an experimental study conducted in vitro. Moringa oleifera and Ziziphus mauritiana were extracted at 10 different concentrations. The test method used was disk diffusion on Mueller-Hinton agar. The treatment group is E. coli ATCC 25922, Ciproflxacin were used as positive controls and discs immersed in 96% ethanol were used as negative controls.The average zone of inhibition of Moringa oleifera leaf extract was 10 mm, while Ziziphus mauritiana leaf extract gave an average of inhibition zone of 14 mm. The average zone of inhibition from positive control is 33 mm. Negative control has no zone of inhibition. Moringa oleifera leaf extract can inhibit the growth of E. coli bacteria at a concentration of 30% with a zone of inhibition of 7 mm, and leaf extract of Ziziphus mauritiana can inhibit the growth of E. coli bacteria at a concentration of 20% with a 12 mm inhibition zone. This proves that Ziziphus mauritiana has more effective antibacterial ability than Moringa oleifera.